2014
DOI: 10.1021/jo500812d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Sulfonamide Derivatives Based on the Oxidation of 2,5-Diethoxy-4-Morpholinoaniline in the Presence of Arylsulfinic Acids

Abstract: Some new sulfonamide derivatives were synthesized in aqueous solutions via anodic oxidation of 2,5-diethoxy-4-morpholinoaniline in the presence of arylsulfinic acids using a commercial carbon anode. In addition, the formation mechanism of the products was discussed. The obtained data show that the electrogenerated quinone diimine undergoes a Michael-type addition reaction with arylsulfinic acids to yield the respective sulfonamide derivatives. In this work, two different types of products (mono- and disulfone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…All of these results are in agreement with the participation of electrogenerated MQI in the Michael addition reaction with BS [28][29][30][31][32][33][34] . Fig.…”
Section: Resultssupporting
confidence: 82%
“…All of these results are in agreement with the participation of electrogenerated MQI in the Michael addition reaction with BS [28][29][30][31][32][33][34] . Fig.…”
Section: Resultssupporting
confidence: 82%
“…Increasing substrate concentration causes the peak current ratio (I pC1 /I pA1 ) to decrease proportionally. Using previous works on the electrochemical oxidation of 2,5-DEMA [26,27] and the present data, it can be said that the cathodic peak C 0 is related to the electrochemical reduction of the product which is produced after trimerization reaction.…”
Section: Resultssupporting
confidence: 57%
“…Investigations indicated that dimerization, trimerization, hydrolysis, and hydroxylation can occur in electrochemical oxidation of amines which is highly dependent on pH of solution [24,25]. Along with our previous works in electrochemical study of amines [23][24][25][26][27][28], diversity of behavior in the electrochemical oxidation of 2,5-diethoxy-4-morpholinoaniline (2,5-DEMA, 1) at various conditions and also the importance of Schiff base reaction [29] prompted us to studying electrochemical oxidation of 2,5-DEMA at various conditions using cyclic voltammetry (CV) and controlled-potential coulometry. The results show that in all pHs electrochemically generated p-quinonediimine (1ox ?…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations